THE IMPACT OF RELIGIOSITY ON PERCEPTIONS OF THE ROLE OF INDEPENDENT COMMISSIONERS IN THE IMPLEMENTATION OF CORPORATE GOVERNANCE IN SHARIA FINANCIAL ENTITIES IN INDONESIA - Mohamad Heykal; Khomsiyah Khomsiyah (Bina Nusantara University, 2023)
The aim of this research is to analyze whether there is an impact of religiosity as well as understanding of Islamic accounting and finance concepts on perceptions of the role of independent commissioners in relation to corporate governance in Islamic financial entities in Indonesia. The research uses primary data by distributing questionnaires to employees in Islamic financial institutions. The results showed that religiosity had a positive and significant effect on perceptions of the role of independent commissioners in corporate governance in Islamic financial institutions, while an understanding of Islamic accounting and finance did not show a significant effect. Research has not been able to prove whether the quality of financial reports can moderate the level of understanding of Islamic accounting and finance because the data obtained from the questionnaire comes from a limited number of Islamic financial institutions.